Reconstruction of the weighted differential operator with point \(δ\)-interaction - Manafov, M.Dzh.; Kablan, A. (Eurasian Mathematical Journal, 2025)
In this article, we provide various uniqueness results for inverse problems of weighted differential operator with point \(δ\)–interaction. In terms of the method of spectral mappings, we also offer step by step strategies for finding their potential and boundary conditions basing either on the Weyl function, on spectral data, or on two spectra.